Binuclear copper(II) complexes discriminating epimeric glycosides and α- and β-glycosidic bonds in aqueous solution - Striegler, Susanne (J Catal, 2016)
Two chiral binuclear copper(II) complexes were synthesized and characterized for the first time as efficient chemoselective catalysts for the hydrolysis of aryl glycosides and disaccharides in aqueous solution at near neutral pH. Under these conditions, discrimination of epimeric aryl α-glycopyranosides was observed both by 29-fold different reaction rates and 3-fold different proficiency of the catalyst. Additionally, large differentiation of the nature of α- and β- glycosidic bond in aryl glycosides as model compounds is apparent, but also noted in selected disaccharides. The influence of the chirality of the complexes and the role of the configuration of the carbohydrate upon interaction with the catalyst is discussed in detail. Lastly, a putative mechanism for the metal complex-catalyzed hydrolysis is derived from the experimental evidence pointing at deprotonation of the hydroxyl group at C-2 as a pre-requisite for glycoside hydrolysis.